Phytochemical and biological investigations of Phyllagathis rotundifolia and Phyllagathis praetermissa / Tan Hooi Poay - Tan, Hooi Poay (2012)
Phyllagathis rotundifolia and P. praetermissa are herbs from the family of Melastomataceae. They are also known as ‘Tapak Gajah’ or ‘Tapak Sulaiman’ and their extracts are employed as substitute of each other in the traditional medicines. Traditionally, a decoction of the plant is used for fever, malaria, stomachache, parturition and as tonic. However, little is known about their chemical composition and no comparative study on their chemical profiles has been reported. Therefore, the phytochemical analysis would be essential to give an insight into their characteristic chemical components as well as fingerprints that can be used to determine the identity and authenticity of plant material. A total of 22 compounds were isolated from the two species. Among these, seven were identified as galloylated cyanogenic glucosides (1-7), 11 were identified as hydrolysable tannins (8-18) and two as ellagic acid derivatives (19, 20). The remaining two were identified as gallic acid (21) and gallic acid methyl ester (22). 20 of these compounds were found present in P. rotundifolia while nine were found in P. praetermissa. The structural identification of these compounds was done using liquid chromatography-mass spectrometry (LC-MS) and nuclear magnetic resonance (NMR) spectroscopy. Their fragmentation patterns were characterised by tandem mass spectrometry (ESI-MSn). Infrared (IR) spectroscopy associated with second derivative spectroscopy and two dimensional infrared (2D-IR) correlation spectroscopy were also employed as a rapid approach for species identification. The cross peak at (1492 cm-1, 1181 cm-1) was found obvious in the synchronous plot of P. rotundifolia but not in P. praetermissa. The IR analysis was also used to characterize the Phyllagathis species collected from different locations based on their peak positions and intensities. Additionally, a reversed-phase high performance liquid chromatography (HPLC) system was used for the profiling of P. rotundifolia and P. praetermissa as well as generating the comparative chromatogram for samples from Pasoh Forest Reserve, Ampang Forest Reserve, Johor Forest Reserve and Bukit Lagong. Generally, the galloylated cyanogenic glucosides (peaks 17-22) were found present in both species except P. praetermissa from Bukit Lagong. However, their presence in P. praetermissa was relatively lower as compared to P. rotundifolia. Similarly, the ellagic acid derivatives 3'-O-methyl-3,4-methylenedioxyellagic acid 4'-O-β-D-glucopyranoside (peak 15) and 3,3',4-tri-O-methylellagic acid 4'-O-β-D-glucopyranoside (peak 16) also exhibited lower intensity in the chromatogram of P. praetermissa than P. rotundifolia. Furthermore, the 1D-IR spectra and HPLC chromatograms were subjected to principal component analysis (PCA) in order to enhance the fingerprinting by converting the huge numerical data to visual plots. The resulting PCA scores plots were able to classify the species into distinct groups which thus can be feasibly applied in quality control measure. The biological potentials of the isolated compounds were evaluated by their neuroprotective activity against H2O2 induced cell damage, in vitro cytotoxicity on CaSki (cervical epidermoid carcinoma cells), HCT 116 (colon carcinoma cells), MCF 7 (breast carcinoma) and methicillin-resistant Staphylococcus aureus (MRSA) inhibitory activity. Compounds 1,2,3,4,6-penta-O-galloyl-β-D-glucose (14), pterocarinin C (17) and prunasin 2',3',4',6'-tetra-O-gallate (7) highly protected the NG108-15 cell line against H2O2 induction. Both 3'-O-methyl-3,4-methylenedioxyellagic acid 4'-O-β-D-glucopyranoside (19) and 3,3',4-tri-O-methylellagic acid 4'-O-β-D-glucopyranoside (20) demonstrated low IC50 values in the CaSki, HCT 116 and MCF 7 carcinoma cell lines. In the case of anti-MRSA activity, prunasin 2',3',4',6'-tetra-O-gallate (7) displayed the lowest MIC value and thus could be further explored as a potential antimicrobial agent.